Glucocerebrosidase Mutations Cause Mitochondrial and Lysosomal Dysfunction in Parkinson’s Disease: Pathogenesis and Therapeutic Implications - Zheng, Wei; Fan, Dongsheng (Frontiers in Aging Neuroscience, 2022)
Parkinson’s disease (PD) is the second most common neurodegenerative disease and is characterized by multiple motor and non-motor symptoms. Mutations in the glucocerebrosidase (GBA) gene, which encodes the lysosomal enzyme glucocerebrosidase (GCase), which hydrolyzes glucosylceramide (GlcCer) to glucose and ceramide, are the most important and common genetic PD risk factors discovered to date. Homozygous GBA mutations result in the most common lysosomal storage disorder, Gaucher’s disease (GD), which is classified according to the presence (neuronopathic types, type 2 and 3 GD) or absence (non-neuronopathic type, type 1 GD) of neurological symptoms. The clinical manifestations of PD in patients with GBA mutations are indistinguishable from those of sporadic PD at the individual level. However, accumulating data have indicated that GBA-associated PD patients exhibit a younger age of onset and a greater risk for cognitive impairment and psychiatric symptoms. The mechanisms underlying the increased risk of developing PD in GBA mutant carriers are currently unclear. Contributors to GBA-PD pathogenesis may include mitochondrial dysfunction, autophagy-lysosomal dysfunction, altered lipid homeostasis and enhanced α-synuclein aggregation. Therapeutic strategies for PD and GD targeting mutant GCase mainly include enzyme replacement, substrate reduction, gene and pharmacological small-molecule chaperones. Emerging clinical, genetic and pathogenic studies on GBA mutations and PD are making significant contributions to our understanding of PD-associated pathogenetic pathways, and further elucidating the interactions between GCase activity and neurodegeneration may improve therapeutic approaches for slowing PD progression.